Innovative inbuilt moving bed biofilm reactor for nitrogen removal applied in household aquarium - Zhou, Xiaolin; Liu, Haicheng; Fan, Xing; Xu, Xinhao; Gao, Yuan; Bi, Xuejun; Cheng, Lihua; Huang, Shujuan; Zhao, Fangchao; Yang, Tang (Frontiers in Microbiology, 2024)
An innovative inbuilt moving bed biofilm reactor (MBBR) was created to protect fish from nitrogen in a household aquarium. During the 90 experimental days, the ammonia nitrogen (NH4 + -N) concentration in the aquarium with the inbuilt MBBR was always below 0.05 mg/L, which would not threaten the fish. Concurrently, nitrite and nitrate nitrogen concentrations were always below 0.5 mg/L and 4.5 mg/L, respectively. However, the blank contrast aquarium accumulated 1.985 mg/L NH4 + -N on the 16 th day, which caused the fish to die. The suspended biofilms could achieve the specific NH4 + -N removal rate of 45.43 g/m 3 /d. Biofilms presented sparsely with filamentous structures and showed certain degrees of roughness.The bacterial community of the suspended biofilms and the sediment were statistically different (P<0.05), reflected in denitrifying and nitrifying bacteria. In particular, the relative abundance of Nitrospira reached 1.4%, while the genus was barely found in sediments. The suspended biofilms showed potentials for nitrification function with the predicted sequence number of ammonia monooxygenase [1.14.99.39] and hydroxylamine dehydrogenase [EC:1.7.2.6] of 220 and 221, while the values of the sediment were only 5 and 1. This study created an efficient NH4 + -N removal inbuilt MBBR for household aquariums and explored its mechanism to afford a basis for its utilization.